2009
DOI: 10.1158/1078-0432.ccr-08-1172
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Apoptosome for Cancer Therapy

Abstract: Apoptosis is a programmed mechanism of cell death that ensures normal development and tissue homeostasis in metazoans. Avoidance of apoptosis is an important contributor to the survival of tumor cells, and the ability to specifically trigger tumor cell apoptosis is a major goal in cancer treatment. In vertebrates, numerous stress signals engage the intrinsic apoptosis pathway to induce the release of cytochrome c from mitochondria. Cytochrome c binds to apoptosis protease activating factor-1, triggering format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 70 publications
2
46
0
Order By: Relevance
“…The mitochondria have been considered to act as a point of integration for apoptotic signals originating from both of these 2 apoptotic pathways. Among various proapoptotic events and factors, the disruption of DY m and release of cyto c are considered critical in mitochondria-mediated apoptosis pathways (34). In this study, silibinin showed a dissipation of DY m in bladder cancer cells as evidenced by JC-1 dye staining, which was accompanied by the release of cyto c from mitochondria to cytosol, as evidenced by immunoblotting, and further activation of downstream effectors caspase-9, caspase-3 and resultant PARP cleavage.…”
Section: Discussionmentioning
confidence: 53%
“…The mitochondria have been considered to act as a point of integration for apoptotic signals originating from both of these 2 apoptotic pathways. Among various proapoptotic events and factors, the disruption of DY m and release of cyto c are considered critical in mitochondria-mediated apoptosis pathways (34). In this study, silibinin showed a dissipation of DY m in bladder cancer cells as evidenced by JC-1 dye staining, which was accompanied by the release of cyto c from mitochondria to cytosol, as evidenced by immunoblotting, and further activation of downstream effectors caspase-9, caspase-3 and resultant PARP cleavage.…”
Section: Discussionmentioning
confidence: 53%
“…20 Ultimately, many of these stressors damage the mitochondria by causing changes in the permeability of the membranes of this organelle, 21 leading to cytochrome c release and apoptosome formation and activation. 22,23 To understand how VOPP1 was activating apoptosis in SCC cells, we first turned to the hypothesis that VOPP1 may Figure 8 The induction of apoptosis from vesicular overexpressed in cancer prosurvival protein 1 (VOPP1) knockdown seen at 72 h post-siRNA transfection is abrogated with the use of the thiol-antioxidant N-acetyl cysteine (NAC) in a dose-dependent manner. (a) On the left axis, caspase-3/ 7 activity in arbitrary luminescence units is shown for control or VOPP1 siRNAs with or without 2.5 mM NAC in squamous cell carcinoma (SCC)-9 cells.…”
Section: Ros Are Required For Apoptosis In Scc Cells Induced By Vopp1mentioning
confidence: 99%
“…53 Inhibition of apoptosis is one of the key features of cancer and in many cancer types where apaf1 loss is evident. 54 It appears that, similarly, Spalax p53 abrogates the activation of apaf1 as an adaptation to escape hypoxia-induced apoptosis. In addition, we provide evidence indicating that besides apaf1 inactivation, hypoxia upregulates mdm2 levels in SApippalax targeting p53 for degradation.…”
Section: Spalax P53 Is Functionally Biased Against Apaf1 and Towards mentioning
confidence: 99%